Optimum allocation of silicone oil in flexible polyurethane foam production (2006)
The high cost of purchasing good quality flexible polyurethane foam called for this project work which examines the possible reduction in the cost of production which will eventually lead to reduction in all overall market cost. Process optimization technique was adopted using gradual chemical variance method for the foam surfactant (silicone oil) to locate the optimum silicone oil quantity required as against the usual practice of 1part of silicone oil to 100 part of polyol for 20kg/m3 density foam. Seven different quantities (1.2g. 1.0g, 0.8g, 0.6g, 0.4, 0.2, 0g) of silicone oil were used to 100g of polyol in the experiments. It was discovered that the quality of the foam produced remained the same as the quantity of silicone oil used was gradually reduced from 1 part per 100parts of polyol to 0.76 parts per 100 parts ofpolyol. Thus the later ratio was obtained as the optimum quantity required for the foam production which was about 24% reduction but still maintaining same quality as that of 1part to 100 parts of polyol when subjected to all the required physical tests.